Organic matter distribution and fluxes within a holm oak (Quercus ilex L.) stand in the Etna volcano - LEONARDI, S.; RAPP, M.; Denes, A. (Plant Ecology, 1992)
Located at 1100 m above sea level, on the western site of the Etna volcano, the ecophysiology of the Mount Minardo holm oak coppice has been investigated for more then twenty years. In this stand, now 31 years old, the above ground biomass amounts to 15000 g m 2 of organic material, including leaves and perennial woody material. During these 31 years, the mean annual production has been around 775 g m 2. The yearly mean litterfall amounts to 310 g m 2, including 200 g m -2 of leaves, mostly two years old. The soil surface is covered by a litter layer amounting to 3150 g m-2. Each year, following Jenny's decomposition rate and field measurements, 290 g m- 2 of the litter turns into CO2, or becomes incorporated in the soil organic matter.
Keywords: Mediterranean forests; organic matter cycling; Quercus ilex L